Behavioral Consequences of a Bifacial Map in the Mouse Somatosensory Cortex - Tsytsarev, Vassiliy (J Neurosci, 2017)
The whisker system is an important sensory organ with extensive neural representations in the brain of the mouse. Patterned neural modules (barrelettes) in the ipsilateral principal sensory nucleus of the trigeminal nerve (PrV) correspond to the whiskers. Axons of the PrV barrelette neurons cross the midline and confer the whisker-related patterning to the contralateral ventroposteromedial nucleus of the thalamus, and subsequently to the cortex. In this way, specific neural modules called barreloids and barrels in the contralateral thalamus and cortex represent each whisker. Partial midline crossing of the PrV axons, in a conditional Robo3 mutant (Robo3(R3–5)cKO) mouse line, leads to the formation of bilateral whisker maps in the ventroposteromedial, as well as the barrel cortex. We used voltage-sensitive dye optical imaging and somatosensory and motor behavioral tests to characterize the consequences of bifacial maps in the thalamocortical system. Voltage-sensitive dye optical imaging verified functional, bilateral whisker representation in the barrel cortex and activation of distinct cortical loci following ipsilateral and contralateral stimulation of the specific whiskers. The mutant animals were comparable with the control animals in sensorimotor tests. However, they showed noticeable deficits in all of the whisker-dependent or -related tests, including Y-maze exploration, horizontal surface approach, bridge crossing, gap crossing, texture discrimination, floating in water, and whisking laterality. Our results indicate that bifacial maps along the thalamocortical system do not offer a functional advantage. Instead, they lead to impairments, possibly due to the smaller size of the whisker-related modules and interference between the ipsilateral and contralateral whisker representations in the same thalamus and cortex. SIGNIFICANCE STATEMENT The whisker sensory system plays a quintessentially important role in exploratory behavior of mice and other nocturnal rodents. Here, we studied a novel mutant mouse line, in which the projections from the brainstem to the thalamus are disrupted. This led to formation of bilateral whisker maps in both the thalamus and the cortex. The two whisker maps crowd in a space normally devoted to the contralateral map alone and in a nonoverlapping fashion. Stimulation of the whiskers on either side activates the corresponding region of the map. Mice with bilateral whisker maps perform well in general sensorimotor tasks but show poor performance in specific tests that require whisker-dependent tactile discrimination. These observations indicate that contralateral, instead of bilateral, representation of the sensory space plays a critical role in acuity and fine discrimination during somesthesis.